Effect of arbuscular mycorhizae on growth and seedling quality index of biofuel species - Jha, Anuradha; Shukla, Ashok; Kumar, Anil; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
An experiment was conducted to study the mutualistic relationship between suitable arbuscular mycorrhizal (AM) fungi with biofuel species namely, Azadirachta indica, Jatropha curcas, Madhuca indica and Pongamia pinnata for increasing their growth, phosphorus (P) uptake and seedling quality at nursery stage. Eleven AM species, isolated from rhizosphere of above mentioned trees and other common plant species of Bundelkhand of central India were used as inoculants. A. indica and M. indica responded positively to the inoculations, while the growth of J. curcas and P. pinnata seedlings was not enhanced. Maximum dependency of plants on AM fungi for dry matter production i.e. mycorrhizal dependency (MD) was recorded in M. indica, followed by A. indica. MD values for most of AM fungi were in the negative range for J. curcas and P. pinnata. The seedling quality of M. indica was improved by all inoculants and A. indica by five inoculants (Acaulospora scrobiculata, Simiglomus hoi, Rhizophagus fasciculatus, Paraglomus occultum and Glomus arborense). Thus, the results highlighted the importance of AM inoculation in M. indica and A. indica at nursery stage. Further, it was indicated that there was no need for AM inoculations in J. curcas and P. pinnata.